Expectations of the youth from the countryside of Palmeira dos Índios admission to higher education / Expectativas do jovem do campo do município Palmeira dos Índios ao ingresso no Ensino Superior - Marcôni Limeira de França (Universidade Estadual de Alagoas, 2016)
This article discusses the expectation of young people from the field to enter Higher Education, since it is a trajectory that means a lot for each student, especially since it is a period linked to the peculiar transformations and adaptations of adolescence. The objective of this study was to expose the expectation of the youth of the municipality of Palmeira dos Índios about the entrance to higher education. For this production, a field research was carried out in the municipality of Palmeira dos Índios in the Canafístula District of Frei Damião, with interviews of teachers, students of the State School José Victorino da Rocha and university students from the rural area, and an analysis of references in books And articles. In this way, the process of change and adaptation to the university presents itself difficult and multidimensional, conditioned to personal and contextual factors. Therefore, for the student who lives in the field to be part of a Higher Education should study a lot and learn all the teachings that basic education provides, because in this place the access to school is more difficult, living in the rural area arises difficulties with transportation, resulted It is based on this research that the youth of the field seeks professional improvement and enter the labor market.